ANALYSIS OF THE FREQUENCY AND DURATION OF THE CLINICAL REMISSION PHASE IN TYPE 1 DIABETES - Todorov, Teodora (Medicinski podmladak, 2024)
Introduction: Clinical remission (CR) phase, in other words euglycaemia in the absence of insulin therapy (complete CR) or with a reduced daily dose of insulin (partial CR) can be achieved in some patients with new-onset type 1 diabetes (T1D) after the introduction of insulin therapy. Unfortunately, we still don't have enough information about the factors influencing the induction and duration of remission.Material and methods: This research included 62 patients with a diagnosis of new-onset T1D, who were treated at the Clinic for Endocrinology, University Clinical Centre of Serbia during 2019 and 2020. Demographic, clinical and laboratory data were acquired from medical records. Descriptive statistical methods, Fisher's exact probability test, Pearson's chi-square test, Student's t test, Mann Whitney U test and Spearman's correlation coefficient were used for the purposes of statistical analysis.Results: CR was inducted in 46.8% of patients and its average duration was 11.2 months. Patients who entered CR had remarkably lower HbA1c values (9.9 ± 2.8 vs 11.8 ± 2.4%; p=0.007) and lost less weight (4 vs 12kg, p
Keywords: new-onset type 1 diabetes; clinical remission; C peptide; GAD